Prácticas preprofesionales e inserción laboral de los egresados de la carrera de Ingeniería Agronómica de la Universidad Técnica de Cotopaxi en la extensión La Maná. Propuesta de rediseño del departamento. - Estrella Angueta, José Fabián (2014)
he work seeks to recover the potential that encloses the spaces of pre- professional practice, transform their strengths and weaknesses and institutionalize those spaces as areas of theoretical and practical articulation. The task consists of describing the work performed by the actors of the academic fields, and propose new debates and strategies aimed to transcend the fragmentation of training as hermetic compartments.(theory - practice)It seeks to characterize the complexity of the field of practice giving it a holistic approach to banish the conception of the theoretical and the practical, to move to a social dimension that requires a reading of theoretical rigor of ethical political positions, as well as dominance and skills in terms of social interventions. The nearest laboratory, object of this work is an experience of pre-professional practice that takes author forward. Describe in this way, the institutional framework in which it develops, its current structure, the theoretical framework, deployed strategies and their main findings. The purpose of the study is to provide concerns, debates and new questions of the acting participants in the educative process of agricultural engineer from the Cotopaxi Technical University. Within the enterprise and professional training in agriculture in the context of new relations of being able to enter in the labor field since experience has advanced in the first efforts to make problematic their practice.